2008
DOI: 10.1016/j.febslet.2008.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Protein flexibility in psychrophilic and mesophilic trypsins. Evidence of evolutionary conservation of protein dynamics in trypsin‐like serine‐proteases

Abstract: To shed light on the molecular features related to cold-adaptation in serine-proteases, we have carried out molecular dynamics simulations of homologous mesophilic and psychrophilic trypsins, with particular attention to evaluation of intramolecular interactions and flexibility.Psychrophilic trypsins present fewer interdomain interactions and enhanced localized flexibility in regions close to the catalytic site. Notably, these regions fit well with the pattern of protein flexibility previously reported for psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…Further details on the MD setup and solvent equilibration, termalization and pressurization steps are reported in ref. [41].…”
Section: Simulationsmentioning
confidence: 95%
“…Further details on the MD setup and solvent equilibration, termalization and pressurization steps are reported in ref. [41].…”
Section: Simulationsmentioning
confidence: 95%
“…In recent years, many studies have focused on the relationship between the structure and function of psychrophilic enzymes and the coldadaptation of psychrophiles. [10][11][12][13][14][15][16] A general theory for coldadaptation has not been formulated. However, psychrophilic enzymes are oen characterized by enhanced exibility at low temperatures to obtain higher catalytic efficiency (k cat /K m ) and to cope with the reduction of metabolic uxes and chemical reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, backbone flexibility profiles diverge slowly, being conserved both at family and superfamily levels [50][51][52]. A recent study, in the context of cold adaptation, has shown that warm-and cold-adapted enzymes belonging to the same family present common dynamics signature related to the same fold but also peculiar differences which may reflect temperature adaptation [53].…”
Section: Discussionmentioning
confidence: 98%